Economics evaluation of erythropoiesis-stimulating agents for the treatment of chemotherapy-induced anaemia in Italy. Issue 2 (12th March 2012) - Gozzo, M.; Lucioni, C.; Mazzi, S.
Abstract : Background: Chemotherapeutic treatment of cancer patients is likely to cause anaemia (chemotherapy-induced anaemia, CIA), which is associated with high medical costs. Current guidelines recommend the use of erythropoiesis-stimulating agents (ESAs) for patients undergoing chemotherapy. Purpose: Following a cost-consequence approach, an economic evaluation was conducted of CIA treatment with ESAs in Italian clinical practice, from the perspective of the National Health Service. Materials and methods: Four pharmacological alternatives were considered: weekly epoetin alfa, epoetin β, darbepoetin α and darbepoetin alfa every three weeks. Clinical outcomes were obtained from the literature. Costs were estimated using a questionnaire addressed to clinicians employed in five hospitals. Data were collected regarding the six most common ESA administration settings (ranging from self-administration to hospitalisation). Resources used in each setting were accounted for. A decision-tree model was used based on these data and on the outcomes from the clinical trials of the drugs considered. The treatment period was set at 12 weeks. Results: The average treatment costs per responding patient (response based on haemoglobin level increment) were (2010, euros): € 4, 291 (darbepoetin α every three weeks), € 5, 051 (weekly darbepoetin α), € 5, 111 (weekly epoetin β), € 5, 810 (weekly epoetin α). Conclusions: Despite study limitations (costs estimates from survey data), in the treatment of CIA among cancer patients in Italy darbepoetin alfa weekly and every three weeks appear to provide more efficient use of healthcare resources compared to epoetin alfa and epoetin β.